Evidence of ubiquitous Alfvén pulses transporting energy from the photosphere to the upper chromosphere - Jiajia Liu (Nature Portfolio, 2019)
Heating of the upper solar atmospheric layers is an open question. Here, the authors show observational evidence that ubiquitous Alfven pulses are excited by prevalent photospheric swirls, which are found to propagate upwards and carry enough energy flux needed to balance the local upper chromospheric energy loss.